Concave Contact Geometry for Enhanced Sealing and Structural Integrity in Ultra-High Pressure Hydrogen Solenoid Valves - Jaeseong Choi; Hwayoung Kim (Applied Sciences)
Ultra-high-pressure hydrogen solenoid valves face a fundamental design challenge of operating across a wide pressure range from 2 MPa to 87.5 MPa. To address the conflicting requirements of effective sealing at low pressures and structural integrity at high pressures, this study proposes a novel concave contact geometry based on Hertzian contact theory. Finite element analysis examines the mechanical relationships between plunger curvature radius (Rₚ), seat curvature radius (Rₛ), and eccentricity (e). Optimization utilizing Latin hypercube sampling and kriging metamodeling yields an optimal design (Rₚ = 5.73 mm, Rₛ = 4.68 mm, e = 0.95 mm) with an Rₚ/Rₛ ratio of 1.22. The optimized concave contact geometry achieves 23.7% higher contact pressure at 2.0 MPa and 42.7% lower maximum equivalent stress at 87.5 MPa compared to conventional rectangular geometry. Experimental validation confirms the concave contact geometry seals at 1.7 ± 0.2 MPa, below the AIS-195 standard requirement of 2.0 MPa and 69.6% lower than the rectangular design (5.6 ± 0.7 MPa). Structural analysis after 87.5 MPa high-pressure exposure reveals no measurable deformation in the concave design, while the rectangular design exhibits permanent deformation of 0.0580 ± 0.007 mm. This integrated methodology provides a framework for optimizing contact geometries in fluid control components operating under extreme pressure conditions, successfully reconciling contradictory requirements across the entire pressure range.